2022
DOI: 10.1007/s10802-021-00892-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Specific Techniques in Behavioral Teacher Training for Childhood ADHD Behaviors: Secondary Analyses of a Randomized Controlled Microtrial

Abstract: Behavioral teacher training is an effective intervention for children with attention-deficit/hyperactivity disorder (ADHD). Intervention effectiveness may be enhanced by including intervention components that carry the strongest evidence for their effectiveness. A previous article of this group showed that both antecedent- (i.e., stimulus-control) and consequent-based (i.e., contingency management) techniques were highly effective in reducing daily teacher-rated, individually selected problem behaviors in a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Furthermore, teacher self-efficacy displayed a marked increase immediately after the training, followed by a slight decline after 5 weeks. This increase is in line with that reported by previous studies on the effectiveness of professional development programs for improving teacher knowledge concerning EBDs (Aguiar et al, 2014; Alshehri et al, 2020; Barbaresi & Olsen, 1998; Corkum et al, 2019; Froelich et al, 2012; Jarque Fernández et al, 2021; Jones et al, 2008; Jongh & Wium, 2021; Kallas et al, 1997; Lasisi et al, 2017; Latouche & Gascoigne, 2019; Maag & Larson, 2004; Miranda et al, 2002; Staff et al, 2022; Syed & Hussein, 2010; Veenman et al, 2019). This increase in knowledge may be a result of the training presented to the participants in this study that was designed, developed, and conducted to meet their overall needs.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, teacher self-efficacy displayed a marked increase immediately after the training, followed by a slight decline after 5 weeks. This increase is in line with that reported by previous studies on the effectiveness of professional development programs for improving teacher knowledge concerning EBDs (Aguiar et al, 2014; Alshehri et al, 2020; Barbaresi & Olsen, 1998; Corkum et al, 2019; Froelich et al, 2012; Jarque Fernández et al, 2021; Jones et al, 2008; Jongh & Wium, 2021; Kallas et al, 1997; Lasisi et al, 2017; Latouche & Gascoigne, 2019; Maag & Larson, 2004; Miranda et al, 2002; Staff et al, 2022; Syed & Hussein, 2010; Veenman et al, 2019). This increase in knowledge may be a result of the training presented to the participants in this study that was designed, developed, and conducted to meet their overall needs.…”
Section: Discussionsupporting
confidence: 91%
“…53 In this sense, interventions directly targeting functional problems, behavioral training for example, should also be recommended. 54 Finally, our results showed that cognitive inflexibility of sADHD increased objective caregiver strain, whose effect was partially mediated through its effect on children's anxiety problems. In comparison, the impaired working memory of sADHD increased objective and subjective aspects of caregiver strain, which is totally mediated by its effect on learning problems of children.…”
Section: Caregiver Strain Of Sadhdmentioning
confidence: 61%
“…The above results are in line with previous longitudinal research, demonstrating that functional sequela including ODD and school disciplinary problems, rather than ADHD symptoms, contributed to the lifetime maternal caregiver strain in adolescents and early adults with ADHD [ 53 ]. In this sense, interventions directly targeting functional problems, behavioral training for example, should also be recommended [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such evaluations should incorporate teacher observations of a student’s behavior and academic functioning (Pliszka & AACAP Work Group on Quality Issues, 2007; Wolraich et al, 2019). Furthermore, teachers are often responsible for providing this group of students appropriate interventions and accommodations in the classroom to support their academic, behavioral, social, and emotional functioning (DuPaul et al, 2020; Mikami et al, 2022; Staff et al, 2022).…”
Section: Attention-deficit/hyperactivity Disorder and The School Envi...mentioning
confidence: 99%